Cigarette smoking reduces platelet reactivity independently of clopidogrel treatment in patients with non-ST elevation acute coronary syndromes - Gabriele Crimi; Alberto Somaschini; Marco Cattaneo; Dominick J Angiolillo; Federico Piscione; Tullio Palmerini; Stefano De Servi (Platelets, 2018)
Smokers receiving clopidogrel show a lower residual platelet reactivity than non-smokers, a phenomenon generally ascribed to smoking-induced increased production of clopidogrel active metabolite, but also associated with the high hemoglobin levels of smokers, which decreases platelet reactivity in tests that measure platelet function in whole blood. We evaluated the impact of cigarette smoking and of hemoglobin levels on platelet reactivity index (PRI) measured by the vasodilator-stimulated phosphoprotein phosphorylation (VASP-P) assay in whole blood samples from patients with non-ST elevation acute coronary syndrome (NSTE-ACS) undergoing percutaneous coronary interventions, both before and after clopidogrel administration. PRI was measured in 718 clopidogrel-naïve NSTE-ACS patients, both before and 1 month after treatment with clopidogrel (75 mg daily). Smokers (n = 347, 48%) had significantly lower mean PRI levels at both baseline (57.7 ± 24.1 vs. 64.8 ± 19.8, p < 0.001) and 1 month (43.4 ± 20.3% vs. 46.8 ± 18.0%, p = 0.017) than non-smokers. After adjusting for potential confounders (age, sex, diabetes, chronic kidney disease, Syntax score>15), the β coefficient of smoke on PRI was −8.51 [−11.90 to −5.11, p < 0.001] at baseline and −3.41 [−6.30 to −0.51, p = 0.02] after 1 month. Hemoglobin was higher in smokers (13.8 ± 1.5 g/dL) than non-smokers (13.1 ± 1.7 g/dL, p < 0.001), but was not significantly correlated with PRI both at baseline (Rho = 0.02, p = 0.60) and at 1 month (Rho = 0.01, p = 0.80). Our analysis confirms that clopidogrel-treated smokers have lower platelet reactivity, measured by the VASP-P assay, compared to clopidogrel-treated non-smokers. However, smokers had lower platelet reactivity already before receiving clopidogrel treatment, suggesting that smoke affects platelet reactivity independently of its potential effect on the pharmacokinetics of clopidogrel. Our data also indicate that such an effect is not mediated by increased hemoglobin levels.